2009
DOI: 10.1016/s1028-4559(09)60323-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Estrogen on the Activity and Growth of Human Osteoclasts In Vitro

Abstract: Estrogen not only suppresses osteoclastogenesis but also inhibits the activity of osteoclasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 15 publications
0
16
2
Order By: Relevance
“…Postmenopausal ERT prevents bone loss and reduces fracture risk 29,30. Estrogen acts mainly by inhibiting osteoclast bone resorption and by preventing the overproduction of osteoclastogenesis-associated cytokines following the postmenopausal estrogen drop 31. …”
Section: Resultsmentioning
confidence: 99%
“…Postmenopausal ERT prevents bone loss and reduces fracture risk 29,30. Estrogen acts mainly by inhibiting osteoclast bone resorption and by preventing the overproduction of osteoclastogenesis-associated cytokines following the postmenopausal estrogen drop 31. …”
Section: Resultsmentioning
confidence: 99%
“…Estrogen is a major regulator of bone growth, influencing the sexual dimorphism of the skeleton and the maintenance of bone mineral homeostasis, which in turn alters both the development of bone strength and the acquisition of peak bone mass (Berger et al, 2010). Estrogens act on bone by regulating bone tissue metabolism, primarily through associations with the promotion of osteoblastic activity and the suppression of osteoclastic resorption (Dempster, 2006, Almeida, 2010, Chen et al, 2009, Zallone, 2006, Tremollieres, 2013). In women, the effects of estrogen on the skeleton appear most notably during adolescence and after menopause.…”
Section: Introductionmentioning
confidence: 99%
“…The duration of contraceptive pill use was significantly shorter in the LMWH-group than in the control group, because combined oral contraceptives (COCs) are contraindicated after the first VTE. Estrogens have been found to be important factors in the regulation of bone metabolism by suppressing osteoclastogenesis and inhibiting bone resorption by osteoclasts [28]. A systematic review with 129 studies concerning hormonal contraception and bone metabolism [29] found, that COCs have no significant effects on BMD in adulthood.…”
Section: Discussionmentioning
confidence: 99%